Blockade of ICAM-1 Improves the Outcome of Polymicrobial Sepsis via Modulating Neutrophil Migration and Reversing Immunosuppression - Yan-jun Zhao; Wen-jing Yi; Xiao-jian Wan; Jun Wang; Tian-zhu Tao; Jin-bao Li; Jia-feng Wang; Xiao-ming Deng (Mediators of Inflammation)
Intercellular adhesion molecule-1 (ICAM-1) is a key adhesion molecule mediating neutrophil migration and infiltration during sepsis. But its role in the outcome of sepsis remains contradictory. The current study was performed to investigate the role of anti-ICAM-1 antibody in the outcome of polymicrobial sepsis and sepsis-induced immune disturbance. Effect of anti-ICAM-1 antibody on outcome of sepsis induced by cecal ligation and puncture (CLP) was evaluated by the survival analysis, bacterial clearance, and lung injury. Its influence on neutrophil migration and infiltration, as well as lymphocyte status, in thymus and spleen was also investigated. The results demonstrated that ICAM-1 mRNA was upregulated in lung, thymus, and spleen of CLP mice. Anti-ICAM-1 antibody improved survival and bacterial clearance in CLP mice and attenuated lung injury. Migration of neutrophils to peritoneal cavity was enhanced while their infiltration into lung, thymus, and spleen was hampered by ICAM-1 blockade. Anti-ICAM-1 antibody also prevented sepsis-induced apoptosis in thymus and spleen. Positive costimulatory molecules including CD28, CD80, and CD86 were upregulated, while negative costimulatory molecules including PD-1 and PD-L1 were downregulated following anti-ICAM-1 antibody administration. In conclusion, ICAM-1 blockade may improve outcome of sepsis. The rationale may include the modulated neutrophil migration and the reversed immunosuppression.